The posterity of Zebrafish in paradigm of in vivo molecular toxicological profiling - Verma, Suresh K; Nandi, Aditya; Sinha, Adrija; Patel, Paritosh; Mohanty, Swabhiman; Jha, Ealisha; Jena, Snehasmita; Kumari, Puja; Ghosh, Aishee; Jerman, Ivan; Chouhan, Raghuraj Singh; Dutt, Ateet; et al. (Biomedicine & pharmacotherapy, 2024)
The aggrandised advancement in utility of advanced day-to-day materials and nanomaterials has raised serious concern on their biocompatibility with human and other biotic members. In last few decades, understanding of toxicity of these materials has been given the centre stage of research using many in vitro and in vivo models. Zebrafish (Danio rerio), a freshwater fish and a member of the minnow family has garnered much attention due to its distinct features, which make it an important and frequently used animal model in various fields of embryology and toxicological studies. Given that fertilization and development of zebrafish eggs take place externally, they serve as an excellent model organism for studying early developmental stages. Moreover, zebrafish possess a comparable genetic composition to humans and share almost 70% of their genes with mammals. This particular model organism has become increasingly popular, especially for developmental research. Moreover, it serves as a link between in vitro studies and in vivo analysis in mammals. It is an appealing choice for vertebrate research, when employing high-throughput methods, due to their small size, swift development, and relatively affordable laboratory setup. This small vertebrate has enhanced comprehension of pathobiology and drug toxicity. This review emphasizes on the recent developments in toxicity screening and assays, and the new insights gained about the toxicity of drugs through these assays. Specifically, the cardio, neural, and, hepatic toxicology studies inferred by applications of nanoparticles have been highlighted.
Keywords: Zebrafish; Models, Animal; modely u zvířat; nanostruktury; savci; dánio pruhované; Animals; Liver; lidé; játra; Nanostructures; Mammals; Humans; zvířata